(untitled) (Scientific journal of the Fergana State University, 2024)
This paper investigates collaborative teaching in an English-for-specific-purposes (ESP) class in our country and reports the findings of the ESP course and a comparative study. It is shown that the experimental group had a more positive attitude and much more motivation toward English learning by the end of the academic year. In recent years, there has been a move away from the traditional approach to language teaching towards cooperative learning. With cooperative learning, students collaborate in pairs or small groups, working towards a common goal. Traditional teaching engages some students, but not all. Cooperative learning structures actively engage every student. By implementing cooperative learning strategies, teachers give their class not only the opportunity to enhance their speaking and listening skills, but also their social and communication skills as teams learn to work towards a common goal together.